2009
DOI: 10.1007/s10544-009-9382-9
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic device for depositing and addressing two cell populations with intercellular population communication capability

Abstract: We present a method for depositing cells in the microchambers of a sealed microfluidic device and establishing flow across the chambers independently and serially. The device comprises a transparent poly(dimethylsiloxane) (PDMS) microfluidic network (MFN) having 2 cell chambers with a volume of 0.49 microL, 6 microchannels for servicing the chambers, and 1 microchannel linking both chambers. The MFN is sealed with a Si chip having 6 vias and ports that can be left open or connected to high-precision pumps. Liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Cell purity of astrocytic culture on PDMS was confirmed by positivity to immunocytochemical staining with glial fibrillar acidic protein GFAP and lack of signal to microglia marker IB4 as previously reported. 16 Immunocytochemical Staining. Primary cells, both neurons and astrocytes, were fixed in 4% paraformaldehyde and 4% sucrose at room temperature (RT) for 10 min.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell purity of astrocytic culture on PDMS was confirmed by positivity to immunocytochemical staining with glial fibrillar acidic protein GFAP and lack of signal to microglia marker IB4 as previously reported. 16 Immunocytochemical Staining. Primary cells, both neurons and astrocytes, were fixed in 4% paraformaldehyde and 4% sucrose at room temperature (RT) for 10 min.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…For example, ports 1, 2, and 5 can be used to flush liquids through chamber A sequentially or in parallel so as to create a biochemical gradient in this chamber. 16 For flushing a chemical in both chambers, port 2 can be used while keeping ports 1, 3, 5, and 6 closed and port 4 open. The volume of each chamber is approximately 0.5 μL, thus minimizing the amount of cells required.…”
mentioning
confidence: 99%
“…In contrast to studying chemical paracrine factors, Lovchick and co-workers' [ 44 ] studied intercellular signalling where microvesicles (organelle containing substances) are the paracrine factors. Their microfl uidic device ( [ 39 ] (B) Mechanism enabling down-regulation of autocrine/paracrine signalling; microfl uidics confers the capacity to tune the relative importance of transport phenomena such that convection rate of ligand dominated over that of diffusion and reaction (ligand-receptor binding).…”
Section: Paracrine Signallingmentioning
confidence: 99%
“…[ 45 ] There have been multiple other strategies described using microfl uidics for co-culture studies. [ 44 ] Notable is a platform enabling co-culture at the single cell level. [ 46 ] Utilising 3D hydrogels is another strategy, where 3D microscale architectures have been developed to mimic the in-vivo environment.…”
Section: Paracrine Signallingmentioning
confidence: 99%
“…Microfluidic devices designed for cell culture have been previously extensively reported (El-Ali et al, 2006; Mehling and Tay, 2014) but are usually either too complex for studying two cell populations or lack one or more desired features for this type of study. One platform has been reported that studies the interaction between microglia and neuroblastoma (Lovchik et al, 2009), but uses perfusion to ensure communication between the two populations of cells, not allowing to replicate diffusion-based events. Other recent platforms allow the study of diffusion-based events (Majumdar et al, 2011; Shi et al, 2013), but either do not ensure that cells are kept physically separated throughout the duration of the experiment—allowing for other types of communication such as juxtacrine signaling—or cannot manipulate the chemical environment of each cell population separately, the stimulation or specific activation of a given population for more complex studies.…”
Section: Introductionmentioning
confidence: 99%